2020
DOI: 10.1210/jendso/bvaa063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Causes of Reduced Cardiorespiratory Fitness in Type 2 Diabetes

Abstract: Abstract Type 2 diabetes (T2D) has been rising in prevalence in the United States and worldwide over the past few decades and contributes to significant morbidity and premature mortality, primarily due to cardiovascular disease (CVD). Cardiorespiratory fitness (CRF) is a modifiable cardiovascular (CV) risk factor in the general population and in people with T2D. Young people and adults with T2D have reduced CRF when compared with their peers without T2D who are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 122 publications
(119 reference statements)
0
18
0
Order By: Relevance
“…It is thought to be mediated by positive changes in the human body tissue profile, reduced adiposity[ 13 ], and an immediate increase in insulin sensitivity and glucose disposal[ 14 ]. However, several studies have shown that impaired oxidative respiration due to mitochondrial dysfunction[ 15 ] underlies the pathogenesis of diabetes reflecting a native genetic state independent of physical activity[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought to be mediated by positive changes in the human body tissue profile, reduced adiposity[ 13 ], and an immediate increase in insulin sensitivity and glucose disposal[ 14 ]. However, several studies have shown that impaired oxidative respiration due to mitochondrial dysfunction[ 15 ] underlies the pathogenesis of diabetes reflecting a native genetic state independent of physical activity[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be mediated by positive changes in the human body tissue profile, reduced adiposity [13], and an immediate increase in insulin sensitivity and glucose disposal [14]. However, several studies have shown that impaired oxidative respiration due to mitochondrial dysfunction [15] underlies (continued) Table 1 the pathogenesis of diabetes reflecting a native genetic state independent of physical activity [16]. Scattered small cross-sectional studies have shown that exercise capacity is inversely associated with impaired glycemic control [17], the metabolic syndrome [18], diabetes [19] and positively associated with glucose disposal rate and insulin sensitivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that lead to hyperglycemia-associated decreases in VO 2peak are incompletely understood. However, low VO 2peak in people with diabetes has been linked with altered function of skeletal muscle, including low muscle blood flow and oxidative capacity ( 16 20 ). Our data from rodent models of hyperglycemia demonstrate that blunted improvements in VO 2peak are associated with impaired remodeling of skeletal muscle toward an aerobic phenotype, leading to lower capillary density and fewer oxidative fibers ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…People with diabetes mellitus type 2 have reduced cardiorespiratory fitness compared to healthy controls, with an association to increased cardiovascular morbidity and mortality. The mechanisms of lower cardiorespiratory fitness in children with diabetes mellitus type 2 are multifaceted and involve interrelated defects in insulin action, mitochondrial dysfunction, skeletal muscle microvasculature, and cardiac dysfunction [55]. In youth with diabetes mellitus type 2, left ventricular size is clearly related to physical fitness, which might counteract adverse effects of poor glycaemic control and, at least according to the study, right ventricular function [56].…”
Section: Cardiorespiratory Fitness In Children With Diabetes Mellitus...mentioning
confidence: 94%